IMPLEMENTASI PEMBELAJARAN PAI (LITERASI, 4C, PPK DAN HOTS DALAM MATERI AQIDAH AKHLAK, DAN AL-QUR’AN HADIS) - Nurhafiza, Nurhafiza; Murhayati, Sri (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study examines the implementation of 21st-century competencies in Islamic Religious Education (PAI), particularly in the subjects of Aqidah Akhlak and Qur’an-Hadith. The competencies discussed include literacy, the 4Cs (critical thinking, creativity, communication, and collaboration), Character Education (PPK), and Higher Order Thinking Skills (HOTS). This research employs a library research method by reviewing various relevant books, journals, and academic studies. The findings indicate that both religious and digital literacy serve as essential foundations for students to understand and connect Islamic teachings with contemporary life challenges. The 4Cs enrich Aqidah Akhlak and Qur’an-Hadith learning by fostering critical thinking, creativity, effective communication, and collaboration. Character Education strengthens students’ moral values, while HOTS encourages them to analyze, evaluate, and create solutions to social issues based on Islamic principles. Thus, integrating 21st-century competencies into PAI not only enhances academic achievement but also nurtures students to become religious, critical, creative, and adaptive individuals in facing the demands of modern times.